Optimized Wireless Charging System with Hybrid Compensation and Solar-Powered FPPT for Efficient Electric Transportation (International Journal of Scientific Research in Science and Technology, 2025)
Wireless charging systems powered by solar energy are a key enabler of sustainable electric transportation. However, conventional Maximum Power Point Tracking (MPPT) introduces high THD and power oscillations, affecting system stability. This paper presents an Optimized Wireless Charging System with a Hybrid Compensation Network, integrating a solar PV source and a Fixed Power Point Tracking (FPPT) controller to enhance power quality. The proposed system supports both Constant Current (CC) and Constant Voltage (CV) modes, ensuring stable and efficient charging under varying load conditions. Unlike MPPT, FPPT maintains a fixed operating point, reducing THD and improving power transfer efficiency. A MATLAB/Simulink 2024a software’s-based simulation validates the system’s performance in wireless charging system, demonstrating significant THD reduction and enhanced charging efficiency. The results confirm FPPT’s effectiveness in low-distortion, high-efficiency EV wireless charging applications.
Keywords: Solar PV Array; boost converter; bidirectional converter; storage battery; high frequency inverter; EV battery; Microgrid; FPPT